Estudo da viabilidade técnica para a utilização do rejeito passivo de carvão mineral, na confecção de blocos de concreto - Tokarski, Rosângela Basso (2022)
The preservation of the environment is a priority in order to offer life with dignity for humanity and its future generations. The aggression caused by the removal of ores and natural products to be destined for various consumption purposes is a reality. The construction industry contributes in several ways to this degradation, and one of them is the manufacture of cement. The coal mining industry also contributes to the environmental damage and one of the ways it happens is the tailings deposits around the coal mines. Nowadays, 38.5% of the energy consumed in the world comes from coal, whose existing reserves have the capacity to supply another 190 years at the current rate of extraction and consumption. In Brazil, mineral coal reserves are located in the South region. The extraction of coal discards around 60% to 70% of the total removed from the mine as tailings. 4,700 tons are discarded in the form of tailings per year, thus generating an enformou environmental liability. The objective of this research is to study the technical feasibility of producing concrete blocks by replacing part of the cement with mineral coal passive waste (MCPW) to be used in civil construction, thus reducing the environmental liability caused by the waste as well as by the manufacturing of cement. The research methodology was divided into three phases, phase 1 used four types of cement: CP IV 32-RS, CP V-ARI, CP II-Z-32, CP II-F-32, testing their compatibility with the cement in percentages of 5% and 10% of MCPW replacing the cement in the concrete mix, thus determining the cement to be used in phases 2 and 3 of the research. The CP II-Z-32 cement showed the best compatibility with the tailings. In phase 2 of the research, three different percentages of MCPW were used, 10%, 20%, 30% of RPCM replacing the cement in the concrete mix, and the reference mix, submitted to different curing times, 28, 60, 90 and 365 days. After curing, they were subjected to physical and mechanical tests, chemical analysis by XRF, mineralogical analysis by XRD, analysis of concrete microstructure by SEM, leaching and solubilization tests. Durability tests: analysis of accelerated aging in the acclimatization chamber, carbonation chamber and internal attack by sulfates. The results indicated that replacing 30% of the cement with passive mineral coal waste in the concrete for molding the blocks meets the specifications of the standard. In phase 3, the blocks were molded, the characterization resulted in blocks with 30% of mineral coal tailings with compressive strength of 5.61 MPa, which is allowed for structural blocks used in buildings of up to 5 floors.